Ceramic selective membrane

Ceramic selective membranes formed by a sol-gel process on porous substrates with additives address the limitations of PFSA materials, providing cost-effective and durable proton-conducting solutions for fuel cells and redox flow batteries.

JP7618514B2Active Publication Date: 2025-01-21UNIV OF WASHINGTON
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021114904
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-02-02
Filing Date
2021-07-12
Publication Date
2025-01-21
Estimated Expiration
2037-02-02

AI Technical Summary

Technical Problem

Current proton-conducting materials, such as perfluorinated sulfonic acid (PFSA) materials, are expensive and require further improvements in operating properties for use in fuel cells and redox flow batteries, while silicate materials have not been developed to be commercially viable due to structural and compositional limitations.

Method used

A method of forming a ceramic selective membrane by applying a ceramic precursor sol to a porous membrane substrate and gelling it using a sol-gel process, creating a selective silica ceramic supported by the substrate, which includes compressible edging for durability and flexibility, and adding additives to enhance properties like ion transport and durability.

Benefits of technology

The ceramic selective membranes provide improved proton conductivity and selectivity, offering a cost-effective alternative to PFSA materials with enhanced durability and flexibility, suitable for use in fuel cells and redox flow batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618514000001
    Figure 0007618514000001
  • Figure 0007618514000002
    Figure 0007618514000002
  • Figure 0007618514000003
    Figure 0007618514000003
Patent Text Reader

Abstract

To develop robust, inexpensive proton-conducting materials.SOLUTION: Disclosed herein are ceramic selective membranes and methods of forming the ceramic selective membranes by forming a selective silica ceramic on a porous membrane substrate. Representative ceramic selective membranes include ion-conductive membranes (e.g., proton-conductive membranes) and gas selective membranes. Representative uses of the membranes include incorporation into fuel cells and redox flow batteries (RFBs) as ion-conductive membranes.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 62 / 290,053, filed February 2, 2016, the disclosure of which is expressly incorporated herein by reference in its entirety.

[0002] Statement of Government License Rights This invention was made with Government support under Contract No. W911NF-13-1-0166 awarded by the Department of Defense through the Army Research Office. The United States Government has certain rights in this invention. [Background technology]

[0003] Fuel cells and redox flow batteries (RFBs) are powerful energy storage technologies that rely on the selective transport of ions across a membrane to generate electrical current. Currently, the standard materials used for membranes in these technologies are perfluorinated sulfonic acid (PFSA) materials, such as those marketed under the name NAFION. These PFSA materials are desirable due to their resistance to harsh environments and ionic conduction properties. However, these materials are relatively expensive, and further improvements in their operating characteristics are desirable.

[0004] Silicate proton conducting materials are known but are not sufficiently developed to be commercially viable.

[0005] One common proton transport mechanism is Grottuss hopping, where hydronium ions "hop" from water molecule to water molecule. This mechanism requires that water rotates and diffuses freely enough to facilitate solvation of the hydronium ions. Therefore, the design of silicate proton conducting materials should have pores of sufficient size to facilitate water molecular motion (i.e., to facilitate hydronium solvation and proton hopping). This size should be larger than a single water molecule (i.e., radius of 0.138 nm) but not so large as to facilitate diffusive transport of other molecules.

[0006] Therefore, the development of robust, inexpensive proton conducting materials is desirable, but significant compositional and structural limitations currently prevent the use of silicate materials as replacements for PFSA materials. Summary of the Invention [Means for solving the problem]

[0007] This Summary is provided to introduce various concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify key features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter.

[0008] In one aspect, a method for forming a ceramic selective membrane is provided. In one embodiment, the method comprises: applying the ceramic precursor sol to a porous membrane substrate; and forming a selective silica ceramic from the ceramic precursor sol by gelling the ceramic precursor sol using a sol-gel process, thereby resulting in a ceramic selective membrane comprising the selective silica ceramic supported by a porous membrane substrate. Includes.

[0009] In another aspect, a ceramic selective membrane is provided that includes a selective silica ceramic supported by a porous membrane substrate.

[0010] In another aspect, there is provided a selective membrane comprising a ceramic selective membrane comprising a selective silica ceramic supported by a porous membrane substrate as previously described.

[0011] In another aspect, a ceramic selective membrane formed by a method according to any of the disclosed method embodiments is provided.

[0012] The foregoing aspects and many of the attendant advantages of this invention will become more readily appreciated as the same become better understood by reference to the following detailed description, when taken in conjunction with the accompanying drawings, in which: [Brief description of the drawings]

[0013] [Figure 1A] 1 is a schematic diagram illustrating a sol-gel strategy using alkali silicates to produce ceramic selective membranes in accordance with certain embodiments disclosed herein. [Figure 1B] FIG. 1 illustrates an exemplary process for producing a ceramic selective membrane with compressible edging ("elastic edging") according to certain embodiments disclosed herein. Step 1: The elastic edging is applied to a pre-sized porous membrane support. A solvent-soluble polymer, such as poly(styrene-isobutylene-styrene) (SIBS), is cast to the size of the support and also defines the active area. The solvent is placed on the edge of the support and then sandwiched by the edging. The solvent partially dissolves the edging, which results in strong adhesion to the support. Step 2: The support is immersed in a silica precursor solution. Step 3: The coated support is immersed in an acid bath. Step 4: The membrane is dried at low temperature (e.g., 60° C.). The process conditions of steps 2-4 can be varied to produce a compressible ceramic selective membrane with specific performance attributes (e.g., proton conductivity, flexibility, durability, pore size, etc.). [Figure 2A]FIG. 1 shows an SEM micrograph of a silica support of a type that can be used as a porous membrane substrate according to certain embodiments disclosed herein. [Figure 2B] FIG. 2 shows an SEM micrograph of a silica selective membrane formed on a silica support according to certain embodiments disclosed herein. [Figure 3A] 1 is a graph showing small angle X-ray scattering (SAXS) profiles of films fitted with a fractal aggregation model. [Figure 3B] 1 is a graph showing pore size distribution based on SAXS modeling. Ideal pore sizes are plotted based on the ionic radii of the ions in the flow battery. The ideal pore size distribution is plotted between the radii of H3O+ and VO2. The known pore size range for NAFION is also plotted. [Figure 4] Figure 1 shows SEM images of the surface and cross-section of an exemplary ceramic selective membrane. The membrane on the right was soaked in a methanol / water mixture to reduce capillary stress before drying. A schematic diagram of the membrane cross-section is also shown. [Diagram 5] FIG. 1 is a graph showing proton conductivity versus VO2 permeability for representative ceramic selective membranes ("SS" is a membrane formed from all sodium silicate; "14 wt% PSS in SS" is a membrane formed with 14 wt% PSS in sodium silicate sol; "NaS-TEOS" is a membrane formed with a combination of sodium silicate and TEOS to form a cohesive composite membrane; "LiS" is a membrane formed in a manner similar to the NaS membrane but with lithium silicate instead of sodium silicate) compared to the commercially available material NAFION 212. [Figure 6A] FIG. 1 graphically illustrates the cycling capacity of an exemplary all-vanadium RFB using an exemplary sol-gel SiO2; an exemplary sol-gel SiO2 + SIBS composite; and a comparative NAFION 115. [Figure 6B] 6B is a graph showing the voltage profile for an RFB including the membrane of FIG. 6A. [Figure 7A]7A-7D show SEM images of a TEOS-sodium silicate membrane according to embodiments disclosed herein. [Figure 7B] 7A and 7B show SEM images of a TEOS-sodium silicate membrane according to embodiments disclosed herein; [Figure 8] FIG. 3A is a graphical representation of the fractal dimensions extracted from the SAXS fitting of a representative membrane (shown in FIG. 3A) using a fractal model. Selectivity (proton conductivity / vanadium ion permeability) is plotted as a function of fractal dimension, showing higher selectivity for lower fractal dimensions. NAFION is plotted for reference. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Disclosed herein are ceramic selective membranes and methods of forming ceramic selective membranes by forming selective silica ceramics on porous membrane substrates. Exemplary ceramic selective membranes include ion-conducting membranes (e.g., proton-conducting membranes) and gas-selective membranes. Exemplary uses for the membranes include incorporation into fuel cells and redox flow batteries (RFBs) as ion-conducting membranes.

[0015] Previous research on silica membranes has focused on thin films, especially those formed entirely from silica. The membranes disclosed herein focus on durability and performance, given their commercial relevance (e.g., replacement of NAFION membranes in RFBs and fuel cells). Thus, the disclosed membranes are relatively thicker because the precursor sol fills the support. In general, silica materials are known to crack when coated onto porous support structures with pore sizes larger than 100 nm. The disclosed membranes are tailored to reduce and eliminate cracking in many ways, including both compositionally (e.g., using polymer additives in the sol that are incorporated into the ceramic matrix) and by "repairing" or "post-processing" by applying a second (or further) layer of ceramic and / or applying a non-ceramic coating to "finish" the membrane.

[0016] The method and many variations are now discussed in more detail. Further below, the compositions (films) formed by the method are also discussed in more detail.

[0017] Method for forming ceramic selective membranes In one aspect, a method for forming a ceramic selective membrane is provided. In one embodiment, the method comprises: applying the ceramic precursor sol to a porous membrane substrate; and forming a selective silica ceramic from the ceramic precursor sol by gelling the ceramic precursor sol using a sol-gel process, thereby resulting in a ceramic selective membrane comprising the selective silica ceramic supported by a porous membrane substrate. Includes.

[0018] See first FIG. 1A, which is a schematic of a sol-gel method using an alkali silicate to produce a ceramic selective membrane according to certain embodiments disclosed herein. In particular, the sol includes sodium silicate, lithium silicate, or potassium silicate as a ceramic precursor sol. In certain embodiments, an "optional" additive is added to the ceramic precursor sol. A "macroporous substrate" (also referred to herein as a porous membrane substrate) is used as a substrate for the formation of a selective silica ceramic sol-gel and ultimately a condensate gel supported by the porous membrane substrate, resulting in a ceramic selective membrane.

[0019] FIG. 1B illustrates an exemplary process for producing a ceramic selective membrane with compressible edging ("elastic edging") according to certain embodiments disclosed herein. Step 1: The elastic edging is applied to a pre-sized porous membrane support. A solvent-soluble polymer, such as poly(styrene-isobutylene-styrene) (SIBS), is cast to the size of the support and also defines the active area. The solvent is placed on the edge of the support and then sandwiched by the edging. The solvent partially dissolves the edging, which results in strong adhesion to the support. Step 2: The support is immersed in a silica precursor solution. Step 3: The coated support is immersed in an acid bath. Step 4: The membrane is dried at low temperature (e.g., 60°C). The process conditions of steps 2-4 can be varied to produce a compressible ceramic selective membrane with specific performance attributes (e.g., proton conductivity, flexibility, durability, pore size, etc.).

[0020] Precursor The precursor is a solution (sol) from which the ceramic is formed. One or more additives can be added to the sol to enable the final ceramic membrane to have special properties, as discussed in more detail below.

[0021] In one embodiment, the ceramic precursor sol comprises an alkaline silicate solution.

[0022] In one embodiment, the alkaline silicate solution is formed from a silicate selected from the group consisting of sodium silicate, lithium silicate, and potassium silicate.

[0023] In one embodiment, the alkali silicate solution has a concentration ranging from 5 wt% to 50 wt%. In one embodiment, the alkali silicate solution has a concentration ranging from 12 wt% to 30 wt%.

[0024] porous membrane base material The porous membrane substrate (sometimes simply referred to herein as "substrate") is the structural base upon which the ceramic is formed. The substrate provides mechanical strength and porous structure. When the ceramic is formed on the substrate, the relatively large pores of the substrate are closed and filled with ceramic until nanometer or angstrom-sized pores remain in the final membrane.

[0025] In one embodiment, the porous membrane substrate has a plurality of pores having a diameter of 10 nm or greater.

[0026] In one embodiment, the porous membrane substrate has a chemical surface functionality that is chemically similar to the ceramic precursor sol.

[0027] In one embodiment, the porous membrane substrate is selected from the group consisting of silica filter paper, polyvinylidene fluoride (PVDF), polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE).

[0028] Compression Edging The compressible edging allows the membrane in certain embodiments to be incorporated into batteries, fuel cells, or other systems where a gasket is required to seal the membrane, and thus is mechanically compressible as well as resistant to the thermal and / or harsh chemical environments in which the membrane is utilized.

[0029] In one embodiment, the method further comprises the step of impregnating an edge portion of the porous membrane substrate with a compressible polymer prior to the step of applying the ceramic precursor sol to the porous membrane substrate.

[0030] In one embodiment, impregnating the edge portions of the porous membrane substrate with the compressible polymer comprises impregnating all edges of the porous membrane substrate with the compressible polymer sufficient to form a gasket that borders the porous membrane substrate.

[0031] In one embodiment, the compressible polymer edging is formed after formation of the ceramic selective membrane (i.e., after the sol-gel process). In a further embodiment, the compressible polymer edging is formed using ultrasonic welding or hot pressing.

[0032] In one embodiment, the edge portion is 1 mm or more in width. In one embodiment, the edge portion is 5 mm or more in width. In one embodiment, the edge portion is 1 cm or more in width.

[0033] In one embodiment, the compressible polymer comprises a thermoplastic elastomeric polymer, hi one embodiment, the thermoplastic elastomeric polymer is selected from the group consisting of poly(styrene-isobutylene-styrene) (SIBS), polyvinylidene fluoride (PVDF), and polydimethylsiloxane (PDMS).

[0034] In one embodiment, the step of impregnating the edge portion of the porous membrane substrate with a compressible polymer comprises a method selected from the group consisting of melting, solution deposition, and in situ reaction.

[0035] Chemical gelation After the sol is coated onto the membrane, the sol must be gelled. In one embodiment, the step of gelling the ceramic precursor sol comprises chemical gelation.

[0036] In one embodiment, the chemical gelation comprises exposing the ceramic precursor sol to an acid solution. In one embodiment, the acid solution is greater than 0.001 N. In one embodiment, the acid solution is greater than 1 N. In one embodiment, the acid solution is greater than 3 N.

[0037] In one embodiment, the acid solution is selected from the group consisting of sulfuric acid, nitric acid, acetic acid, hydrochloric acid, methanesulfonic acid, and phosphoric acid.

[0038] In one embodiment, the chemical gelation process is completed in less than 1 hour. In one embodiment, the chemical gelation process is completed in less than 24 hours. In one embodiment, the chemical gelation process is completed in less than 96 hours.

[0039] In one embodiment, the step of chemical gelation further comprises exposing the ceramic precursor sol to a temperature in the range of 20° C. to 100° C. after exposing the ceramic precursor sol to the acid solution. It is important to keep the temperature low in this embodiment to avoid sintering or calcination, which would compromise the durability of the final ceramic selective membrane.

[0040] Heat gelation In one embodiment, gelling the ceramic precursor sol includes exposure to a temperature ranging from 20° C. to 100° C. It is important to keep the temperature low in this embodiment to avoid sintering or calcination, which would compromise the durability of the final ceramic selective membrane. In a further embodiment, gelling does not include exposure to an acid.

[0041] In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.1 nm to 10 nm in diameter. The pore size is the final pore size of the ceramic selective membrane including all layers of ceramic and any post processing layers (e.g., "finishing" alkyl layers). In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.1 nm to 5 nm in diameter. In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.1 nm to 1 nm in diameter. In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.5 nm to 1 nm in diameter.

[0042] In one embodiment, the ceramic selective membrane has a thickness in the range of 0.1 mm to 1 mm. In one embodiment, the ceramic selective membrane has a thickness in the range of 0.1 mm to 0.5 mm. In one embodiment, the ceramic selective membrane has a thickness in the range of 0.2 mm to 0.4 mm.

[0043] In certain embodiments, multiple layers of ceramic are deposited to provide a thicker ceramic layer on the support and / or improve the durability of the final film. In one embodiment, two coats of ceramic are applied. In a further embodiment, three coats of ceramic are applied. Multiple coats result in a denser and more defect-free film structure. As an example, with a 27 wt% sodium silicate solution, a single coat of ceramic may be sufficient to produce a sufficiently dense and defect-free coating. More than one coat is required for sodium silicate concentrations of 15 wt% and 5 wt% when using a 250 μm substrate.

[0044] In one embodiment, the method comprises: applying the ceramic precursor sol to a selective silica ceramic supported by a porous membrane substrate; and Gelling the ceramic precursor sol to provide a dual-coated selective silica ceramic supported by a porous membrane substrate. The method further includes depositing at least one additional layer of ceramic by

[0045] In a further embodiment, the step of depositing at least one additional layer of ceramic includes repeating the step of depositing at least one additional layer of ceramic a second time to provide a triple-coated selective silica ceramic supported by the porous membrane substrate.

[0046] Additives As previously discussed, additives are added to the sol to enable certain desired properties of the film when formed.

[0047] In one embodiment, the ceramic precursor sol further comprises an additive selected from the group consisting of a selectivity additive configured to increase the ion transport properties of the ceramic selective membrane, a durability additive configured to improve the durability of the ceramic selective membrane, and a catalytic additive configured to impart catalytic properties to the ceramic selective membrane.

[0048] In one embodiment, the additive is a selectivity additive selected from the group consisting of ion-conducting polymers and gas-conducting polymers. To improve selectivity, in certain embodiments, the polymer is an additive used to facilitate selective ion transport. For example, proton-conducting polymers such as polystyrene sulfonate (PSS), polydiallyldimethylammonium chloride (polyDADMAC), sulfonated nanocrystalline cellulose, sulfonated polyetheretherketone (SPEEK), sulfonated polybenzimidazole (S-PBI) or perfluorosulfonic acid (PFSA). In other embodiments, the additive is a polymer (i.e., polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyethylene glycol, and others) that promotes selective transport of other molecules (e.g., gases or other ions). Any additive polymer is soluble or dispersible in the alkaline ceramic solution. Furthermore, they must be able to handle harsh environments or be protected from degradation by oxides.

[0049] In one embodiment, the additive is a durability additive selected from the group consisting of a low Young's modulus polymer configured to provide increased flexibility to the ceramic selective membrane and a high Young's modulus polymer configured to provide increased durability to the ceramic selective membrane.

[0050] In certain embodiments, the durability additive is a polymer. A low Young's modulus polymer additive provides flexibility to the final film, while a high Young's modulus provides improved durability to the final film. They are soluble or dispersible in alkaline ceramic solutions that can handle the harsh environments previously defined or be protected from oxidation degradation. Exemplary durable polymer additives include polyvinyl alcohol, polyacrylic acid, polyacrylamide, and polyethylene glycol, as well as combinations and copolymers thereof.

[0051] In one embodiment, the additive is a catalytic additive selected from the group consisting of catalytic particles added to the ceramic precursor sol and catalytic particles formed in the ceramic precursor sol. The catalytic additive is selected from the following schemes: (1) adding catalytic nano- or micro-particles to the sol; (2) forming catalytic particles in the sol (e.g., before gelation / self-assembly); (3) forming catalytic particles in the sol-gel; and (4) applying / coating catalytic particles on the surface of the active area after the surface of the active area is cured. Platinum is an example of a catalytic additive. The catalytic additive must be able to handle the harsh environment to which the membrane is exposed (if contained externally) or must be protected from degradation by the ceramic membrane (if contained internally). In one embodiment, the catalytic additive is 10 vol% or less of the membrane.

[0052] Post-treatment of the membrane Post-treatment of the membrane is another route to impart specific properties to the membrane. Post-treatments can be used together with or in place of additives to produce membranes with specific properties.

[0053] In one embodiment, the method further comprises depositing a finishing layer on the selective silica ceramic supported by the porous membrane substrate to provide a finished coated selective silica ceramic supported by the porous membrane substrate.

[0054] In one embodiment, depositing the finishing layer comprises treating a selective silica ceramic supported by a porous membrane substrate with a silica-based compound having hydrolyzable groups (e.g., tetraethyl orthosilicate).

[0055] In one embodiment, the step of treating the selective silica ceramic supported by the porous membrane substrate by applying a silica-based compound having hydrolyzable groups further comprises exposing the silica-based compound having hydrolyzable groups to water after applying the silica-based compound having hydrolyzable groups to the selective silica ceramic supported by the porous membrane substrate.

[0056] In one embodiment, the method further comprises treating the ceramic selective membrane with an agent selected from the group consisting of ionic conductivity enhancers, molecular selectivity enhancers, catalysts, and durability enhancers.

[0057] In one illustrative embodiment, a sulfonated poly(styrene-isobutylene-styrene) (S-SIBS) coating has been shown to improve the molecular selectivity of membranes in a flow battery environment. S-SIBS is referenced in FIG. 1B, FIG. 6A, and FIG. 6B. S-SIBS can be applied using any coating method (e.g., drop coating). In an illustrative method, the outside of a dry (fully formed) membrane was coated with <100 μm of S-SIBS polymer to reduce defects.

[0058] The membrane can also be functionalized using standard silane coupling agents, including silanes with sulfonic acid groups to improve proton conductivity or molecular selectivity. Illustrative compounds include 3-trihydroxysilyl-1-propanesulfonic acid and triethoxy(hexyl)silane.

[0059] Other embodiments include silanes with long alkane groups to improve durability or reduce pore size. Exemplary silanes with alkane groups are tetraethyl orthosilicate (TEOS) and triethoxy(hexyl)silane.

[0060] In an illustrative method, the exterior of the membrane dipped in the sol was coated with TEOS and allowed to dry at room temperature.

[0061] In another illustrative method, a dry membrane was coated with a polystyrene sulfonate (PSS) solution and allowed to dry.

[0062] In one embodiment, the method further comprises exposing the ceramic selective membrane to a liquid of lower surface tension after gelling the ceramic precursor sol, which helps reduce the amount of surface cracks in the final membrane due to lower capillary stresses.

[0063] In such an embodiment, instead of exposing the film to acid after the sol has been applied and then placing it in an oven (or at room temperature), the film is exposed to a lower surface tension fluid. In one method, there is only a single exposure step in water, methanol or a 50 / 50 water / methanol mixture. In another variation to the method, sequential immersions in water, a 50 / 50 water / ethanol mixture and then methanol are used.

[0064] Pretreatment of porous membrane substrate In one embodiment, the method further comprises applying a pretreatment to the porous membrane substrate prior to the step of applying the ceramic precursor sol to the porous membrane substrate.

[0065] In one embodiment, the pretreatment is selected from the group consisting of acids and polymers. In an exemplary embodiment, the substrate is not first coated with silica sol, but instead is coated with an acid or polymer (polystyrene sulfonic acid). In one method, this pre-coating is low temperature (T<100° C.) and the freshly coated substrate is then used in the standard sol / sol-gel process disclosed herein. In an alternative method, the pre-coating is not dried, but instead is directly immersed in silica sol.

[0066] Ceramic selective membrane composition In addition to the method of forming the ceramic selective membrane, the membrane itself is considered herein as a composition. Essentially, any membrane formed by the disclosed method is considered an embodiment of the disclosed aspects. Thus, the composition and characteristics of the membrane derive from the preceding discussion of the method.

[0067] In another aspect, a ceramic selective membrane is provided that includes a selective silica ceramic supported by a porous membrane substrate.

[0068] In one embodiment, the porous membrane substrate is selected from the group consisting of silica filter paper, polyvinylidene fluoride (PVDF), polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE).

[0069] In one embodiment, the porous membrane substrate has a plurality of pores having a diameter of 10 nm or greater.

[0070] In one embodiment, the ceramic selective membrane further comprises a compressible polymer edging along at least a portion of the edge of the porous membrane.

[0071] In one embodiment, the ceramic selective membrane further comprises a compressible polymer edging along all edges of the ceramic selective membrane, defining a gasket.

[0072] In one embodiment, the edge portion is 1 mm or more in width. In one embodiment, the edge portion is 5 mm or more in width. In one embodiment, the edge portion is 1 cm or more in width.

[0073] In one embodiment, the compressible polymer comprises a thermoplastic elastomeric polymer, hi one embodiment, the thermoplastic elastomeric polymer is selected from the group consisting of poly(styrene-isobutylene-styrene) (SIBS), polyvinylidene fluoride (PVDF), and polydimethylsiloxane (PDMS).

[0074] In one embodiment, the selective silica ceramic comprises multiple layers of selective silica ceramic material.

[0075] In one embodiment, the ceramic selective membrane further comprises a finishing layer coating the selective silica ceramic.

[0076] In one embodiment, the finishing layer comprises an alkyl-containing compound.

[0077] In one embodiment, the selective silica ceramic comprises an additive selected from the group consisting of a selectivity additive configured to increase the ion transport properties of the ceramic selective membrane, a durability additive configured to improve the durability of the ceramic selective membrane, and a catalytic additive configured to add catalytic properties to the ceramic selective membrane.

[0078] In one embodiment, the selective silica ceramic comprises a selective additive selected from the group consisting of ion-conducting polymers and gas-conducting polymers.

[0079] In one embodiment, the additive is a durability additive selected from the group consisting of a low Young's modulus polymer configured to provide increased flexibility to the ceramic selective membrane and a high Young's modulus polymer configured to provide increased durability to the ceramic selective membrane.

[0080] In one embodiment, the additive is a catalytic additive selected from the group consisting of catalytic particles and catalytic compounds incorporated into a selective silica ceramic.

[0081] In one embodiment, the ceramic selective membrane further comprises a surface treatment layer on the selective silica ceramic comprising an agent selected from the group consisting of ionic conductivity enhancers, molecular selectivity enhancers, catalysts, and durability enhancers.

[0082] Ceramic selective membrane characteristics The characteristics of ceramic selective membranes are unique and enable their use in batteries, fuel cells, and the like.

[0083] In one embodiment, the ceramic selective membrane has an average pore size in the range of 0.5 nm to 2 nm, as determined by fitting a polydisperse fractal model to the small angle x-ray scattering profile.

[0084] In one embodiment, the fractal nature of the pore structure is about 3, as determined by fitting a polydisperse fractal model to the small angle X-ray scattering profile (see, e.g., FIG. 8). In one embodiment, the fractal nature of the pore structure is in the range of about 1.4 to about 3.

[0085] In one embodiment, the galvanodynamic proton conductivity measured in an h-cell in 4M H2SO4 ranges from 0.001 S / cm to 1 S / cm. In one embodiment, the galvanodynamic proton conductivity measured in an h-cell in 4M H2SO4 ranges from 0.05 S / cm to 1 S / cm.

[0086] In one embodiment, the permeability of vanadium(IV) sulfate hydrate ions across the ceramic selective membrane is 1×10 cm 2 / min to 8×10-4cm 2 / min. In one embodiment, the permeability of vanadium(IV) sulfate hydrate ions across the ceramic selective membrane is measured to be in the range of 1×10-6 cm2 / min to 1×10-5cm 2 / min range.

[0087] In one embodiment, the proton / vanadium ion selectivity of the ceramic selective membrane is defined by the ratio: proton conductivity / vanadium ion permeability, and is 3,500 S·min / cm 3 to 58,000 S·min / cm 3 In one embodiment, the proton / vanadium ion selectivity of the ceramic selective membrane is defined by the ratio: proton conductivity / vanadium ion permeability, and is measured to be 15,000 S·min / cm 3 to 30,000 S·min / cm 3 It is measured to be.

[0088] In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.1 nm to 10 nm in diameter. The pore size is the final pore size of the ceramic selective membrane including all layers of ceramic and any post processing layers (e.g., "finishing" alkyl layers). In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.1 nm to 5 nm in diameter. In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.1 nm to 1 nm in diameter. In one embodiment, the ceramic selective membrane comprises pores in the size range of 0.5 nm to 1 nm in diameter.

[0089] In one embodiment, the ceramic selective membrane has a thickness in the range of 0.1 mm to 1 mm. In one embodiment, the ceramic selective membrane has a thickness in the range of 0.1 mm to 0.5 mm. In one embodiment, the ceramic selective membrane has a thickness in the range of 0.2 mm to 0.4 mm.

[0090] In one embodiment, the selective silica ceramic disposed on the surface of the porous membrane substrate has a thickness of 0.5 μm to 750 μm.

[0091] Selective membrane incorporating ceramic selective membrane In another aspect, selective membranes are provided that include ceramic selective membranes that include a selective silica ceramic supported by a porous membrane substrate as previously described.

[0092] The disclosed membranes can be used in any existing or future developed system where separation is desired in a manner in which the membrane can be configured (e.g., based on pore size, selectivity of transport across the membrane, etc.). In one embodiment, the selective membrane is a type of selective membrane selected from the group consisting of battery membranes (e.g., RFB membranes), fuel cell membranes, food processing membranes (e.g., for purifying glucose from starch, for clarifying fruit juice, separation of gelatin from proteins, and separation of curds and whey), reverse osmosis membranes, gas separation membranes (e.g., separation of nitrogen from air, separation of carbon dioxide from natural gas, and separation of hydrogen from light petroleum products), and bioseparation membranes (e.g., dialysis membranes, purification of viruses / bacteria, separation of plasma from blood, and purification of pharmaceuticals to desalt and concentrate antibiotics).

[0093] In one embodiment, the selective membrane is an ion-conducting membrane for a flow battery.

[0094] In one embodiment, the selective membrane is an ion-conducting membrane for a fuel cell.

[0095] Membranes produced by the described method In another aspect, a ceramic selective membrane formed by a method according to any of the disclosed method embodiments is provided.

[0096] In another aspect, a selective membrane is provided that includes a ceramic selective membrane according to any of the disclosed embodiments.

[0097] In one embodiment, the selective membrane is a type of selective membrane selected from the group consisting of battery membranes, fuel cell membranes, food processing membranes, reverse osmosis membranes, gas separation membranes and bioseparation membranes.

[0098] In one embodiment, the selective membrane is an ion-conducting membrane for a flow battery.

[0099] In one embodiment, the selective membrane is an ion-conducting membrane for a fuel cell.

[0100] The following examples are given for the purpose of illustrating but not limiting the described embodiments. EXAMPLES

[0101] Exemplary methods of forming the films and characterization of the films are disclosed below.

[0102] An exemplary membrane is produced using the process outline in Figure 1A. It includes immersing a macroporous support (e.g., a silica filter substrate) in a 27 wt% sodium silicate solution for 30 seconds to promote wicking. The immersed support is then immersed in 3N sulfuric acid for 8 hours, after which it is removed and dried in an oven at 70°C for 2 hours. The process is then repeated at least once to further reduce pore size and improve durability while reducing cracking.

[0103] Referring to FIG. 1B, an exemplary membrane production process is shown in four steps. Step 1: An elastic edging is applied to a pre-sized ceramic macroporous support. A solvent-soluble polymer, such as poly(styrene-isobutylene-styrene) (SIBS), is cast to the size of the membrane while also defining the active area. The solvent is placed on the edge of the membrane and then sandwiched by the polymer edging. The solvent partially dissolves the edging, which results in strong adhesion to the support. Step 2: The membrane is immersed in a silica precursor solution. Step 3: The membrane is immersed in an acid bath. Step 4: The membrane is dried at low temperature (e.g., 60° C.). The process conditions of steps 2-4 can be varied to produce compressible ceramic proton conducting membranes with specific performance attributes.

[0104] FIG. 2A is an SEM micrograph of a silica support of a type usable as a porous membrane substrate according to certain embodiments disclosed herein (specifically of the type disclosed above with respect to FIG. 1A). FIG. 2B is an SEM micrograph of a silica selective membrane formed on a glass fiber support according to certain embodiments disclosed herein (specifically of the type disclosed above with respect to FIG. 1A). FIGS. 2A and 2B are surface SEM images of a material coated with a 10 nm layer of Au / Pd to reduce charging during imaging. The glass fiber support is manufactured by Pall Corp and is a binderless borosilicate glass fiber support ("A / C type"). The nominal pore size is 1 micron and the thickness is 254 microns.

[0105] Figure 3A: Small angle X-ray scattering (SAXS) profile of the membrane fitted with a fractal aggregation model. Figure 3B: Pore size distribution based on SAXS modeling. Ideal pore sizes based on the ionic radii of the ions in the flow battery are observed. The ideal pore size distribution is + and VO2. The known pore size range for NAFION is also seen. All of these samples were processed using the method of FIG. 1 discussed above. The SAXS profile in FIG. 3A is for a membrane formed using nitric acid. In FIG. 3B, the only difference between the curves is the acid form. The following average radii (in Angstroms) were found for the corresponding acids: 4.5=CH3COOH (acetic acid), 5.0=HCl, 6.0=CH3SO4 (methanesulfonic acid), 7.2=H3PO4, 8.1=HNO3. These figures demonstrate that we can achieve a variety of pore sizes depending on the processing conditions. NAFION is included in FIG. 3B as a reference. Considering these data, the ideal pore size (radius) for a ceramic selective membrane is 3 nm or less.

[0106] FIG. 4: SEM images of the surface and cross section of an illustrative ceramic selective membrane. The membrane on the right was soaked in a methanol / water mixture to reduce capillary stress before drying. A schematic diagram of the membrane cross section is also shown. This figure shows that we can generate a dense silica structure in the membrane. These may have surface cracks, but do not have bridging cracks that would impair membrane performance. Furthermore, surface cracks can be reduced by soaking the membrane in a water / methanol bath before drying. These samples were made using the standard process previously described with respect to FIG. 1A. The acid used in both was 3N H3PO4, and they were made using two soaking cycles (also described previously). The samples without post-wash were dried normally at 70° C. The post-washed ones were soaked in a 50 / 50 v / v water / methanol mixture for 1 hour before and then dried at 70° C. (This soaking was only done for the last cycle).

[0107] FIG. 5 plots proton conductivity versus VO2 permeability for representative ceramic selective membranes ("NaS" is a membrane formed from all sodium silicate; "14 wt% PSS in NaS" is a membrane formed with 14 wt% PSS in sodium silicate sol; "NaS-TEOS" is a membrane formed with a combination of sodium silicate and TEOS to form a cohesive composite membrane; "LiS" is a membrane formed in a similar manner to the NaS membrane but with lithium silicate instead of sodium silicate) compared to the commercially available material NAFION 212.

[0108] FIG. 5 illustrates a number of key performance attributes for a flow battery for the formulations previously discussed.

[0109] Proton conductivity is tested with a dynamic current sweep from 0 mA to 200 mA in 4M H2SO4 solution. Measurements are performed in an h-cell using a Luggin capillary, platinum leads and an Ag / AgCl reference electrode.

[0110] Vanadium permeability is also performed in an h-cell with 1.5M VOSO4 and 2M H2SO4 on one side and 1.5M MgSO4 and 2M H2SO4 on the other side. Aliquots of liquid are taken as a function of time to track vanadium diffusion across the membrane. Vanadium is blue in colour and the concentration can be determined using UV-vis.

[0111] Low permeability and high conductivity is ideal, but high conductivity and modest permeability are also valuable to allow the battery to charge faster. NaS membranes are a good candidate because they are similar to NAFION but dramatically cheaper to produce.

[0112] NAFION 212 is defined as 2 mil thick NAFION (tetrafluoroethylene-perfluoro-3,6-dioxa-4-methyl-7-octene sulfonic acid copolymer). Pure NaS is a sodium silicate sample processed in the same manner as previously described with respect to FIG. 1A (i.e., two coats and a 70° C. drying step).

[0113] PSS, 14 wt% in NaS, is polystyrene sulfonate and sodium silicate. In this case, PSS is mixed with sodium silicate prior to wicking into the substrate. Since PSS acts as an acid, an acid soak step is not used in this method. About 1 minute after mixing the PSS and NaS, the substrate is immersed and the composite solution wicks into the macroporous substrate. The membrane is then removed and allowed to gel / dry at room temperature for 1 week.

[0114] The lithium silicate (LiS) sample was processed in the same manner as the sodium silicate in Figure 1A. It is Lithisil™ 25 (23% lithium silicate and 77% water). The acid used was 3N H3PO4 for 24 hours. It was not dried but instead immediately removed and tested.

[0115] NaS-TEOS is processed in a different way. In this case, the macroporous substrate is immersed in sodium silicate (which is slightly basic) for 30 seconds (for wicking) and then placed on the sheet. TEOS is then added as a top layer, which reacts with water (hydrolysis) and the base acts as a catalyst. The TEOS and sodium silicate aggregate to form a dense structure within the substrate. Part of the TEOS evaporates during gelation / drying. The gelation / drying process is left at room temperature for one week.

[0116] All of the samples tested in FIG. 2 of active area and 5cm 2 The total area including edging is:

[0117] Figure 6A graphically illustrates the cycling capacity of an exemplary all-vanadium RFB using an exemplary sol-gel SiO2; an exemplary sol-gel SiO2 + SIBS composite; and a comparative NAFION 115. Figure 6B illustrates the voltage profile for an RFB including the membrane of Figure 6A.

[0118] 7A and 7B are SEM images of a TEOS-sodium silicate membrane according to embodiments disclosed herein, where Fig. 7A is a top view and Fig. 7B is a cross-sectional close-up.

[0119] Figure 8 shows as a graph the fractal dimensions extracted from the SAXS fitting of a representative membrane using the fractal model (shown in Figure 3A). The selectivity (proton conductivity / vanadium ion permeability) is plotted as a function of fractal dimension showing higher selectivity for lower fractal dimensions. NAFION is plotted for reference. The method used here is the same as described in Figure 3A, and the fractal dimensions correspond to the following acids: 2.97 = CH3SO4, 1.6 = H3PO4, 2.88 = CH3COOH, 2.49 = H2SO4, 2.67 = HNO3, 2.4 = HCl.

[0120] Any approximation terminology, such as "about," "approximately," and "substantially," indicates that the subject matter can be modified by plus or minus 5% and still fall within the described embodiments.

[0121] While exemplary embodiments have been illustrated and described, it will be recognized that various changes can be made therein without departing from the spirit and scope of the invention.

Claims

1. immersing a porous membrane substrate in a ceramic precursor sol comprising an alkaline silicate solution formed from a silicate selected from the group consisting of sodium silicate, lithium silicate and potassium silicate, wherein the porous membrane substrate is a silica filter substrate; and forming a silica ceramic from the ceramic precursor sol by gelling the ceramic precursor sol using a sol-gel process, thereby resulting in a ceramic selective membrane, which is a proton conducting membrane comprising a silica ceramic supported by a porous membrane substrate. Including, The porous membrane substrate has a plurality of pores having a diameter of 10 nm or more, gelling the ceramic precursor sol comprises chemical gelling, the chemical gelling comprising exposing the ceramic precursor sol to an acid solution; the step of gelling the ceramic precursor sol comprises exposing the sol to a temperature in the range of 20° C. to 100° C.; The method for forming a ceramic selective membrane, which is a proton conducting membrane, wherein the ceramic precursor sol further comprises an additive of polystyrene sulfonate (PSS).

2. 2. The method of claim 1, wherein the alkaline silicate solution has a concentration in the range of 5 wt% to 50 wt%.

3. immersing the silica ceramic supported by the porous membrane substrate in the ceramic precursor sol; and Gelling the ceramic precursor sol to provide a dual-coated silica ceramic supported by a porous membrane substrate. The method of claim 1 further comprising depositing at least one additional layer of ceramic by

4. 4. The method of claim 3, further comprising repeating the step of depositing at least one additional layer of ceramic a second time to result in a triple-coated silica ceramic supported by the porous membrane substrate.

5. 10. The method of claim 1, further comprising exposing the ceramic selective membrane to water, methanol, or a 50 / 50 water / methanol mixture after gelling the ceramic precursor sol.

Citation Information

Patent Citations

  • Room temperature curing surface coatings and method of manufacture and application

    JP1992506769A

  • Silica gel composition, membrane electrode assembly with proton-exchange membrane and fuel cell

    JP2004307814A

  • Polymer electrolyte membrane

    JP2007080524A

  • Proton conductive film and manufacturing method thereof, and fuel cell and chemical sensor using the same

    JP2009016267A

  • Barrier membrane for redox flow battery and manufacturing method thereof

    JP2012248408A